INTERNASIONALISASI DATA KECELAKAAN LALULINTAS JALAN DI INDONESIA - Susilo, Budi Hartanto; Santosa, Wimpy (Jurnal Transportasi, 2008)
AbstractÂ Â Â Â Â Â Â Â Â Â Â Â Without significant efforts to reduce the number of accidents which causes deaths, the fatal accidents in traffic road, will follow the prediction of WHO (1999) becoming âthe third biggest diseaseâ after ischaemic heart disease and unipolar major depression in 20 years period ahead until year 2020. Since the record system of road traffic accidents in Indonesia is not as same as the record system of international traffic accident, then the data of road traffic accident in Indonesia has to be converted. Based on the results of a simple study in Bandung, these review used conversion factor of 1.25 to convert data of fatal accident in Indonesia. By using this conversion factor, it is found that the number of road accident fatalities in Indonesia is 36,000 persons per year, with the rate of accident is 33 persons per 10,000 vehicles.Keywords: traffic accident, fatal accident, accident rate, data of accident, and conversion factor.